Myocardial blood flow and cardiac sympathetic innervation in young adults late after arterial switch operation for transposition of the great arteries. (15th January 2020) - Possner, Mathias; Buechel, Ronny R.; Vontobel, Jan; Mikulicic, Fran; Gräni, Christoph; Benz, Dominik C.; Clerc, Olivier F.; Fuchs, Tobias A.; Tobler, Daniel; Stambach, Dominik; Greutmann, Matthias; Kaufmann, Philipp A.
Abstract: Background: The arterial switch operation (ASO) for repair of transposition of the great arteries (TGA) requires transection of the great arterial trunks and re-implantation of the coronary arteries into the neoaortic root resulting in cardiac sympathetic denervation which may affect myocardial blood flow (MBF) regulation. The aims of the present study were to evaluate sympathetic (re-)innervation in young adults after ASO and its impact on MBF. Methods: Twelve patients (age 22.5 ± 2.6 years) after ASO for TGA in the neonatal period and ten healthy controls (age 22.0 ± 1.7 years) were included. Positron emission tomography (PET) was used for measuring cardiac sympathetic innervation with [ 11 C] meta -hydroxyephedrine (mHED) and MBF with [ 15 O]H2 O PET at rest, during adenosine stimulation, and during sympathetic stimulation with cold pressor test. Cold pressor-induced MBF response capacity was calculated as maximal global MBF over peak rate-pressure product multiplied by 10′000. Results: Global [ 11 C]mHED uptake was significantly lower in patients compared to controls (7.0 ± 2.3 versus 11.8 ± 2.1%/min, p  < 0.001). Global MBF was lower in patients compared to controls at rest and during adenosine-induced hyperemia (0.66 ± 0.08 versus 0.82 ± 0.15 ml/min/g, p  = 0.005; 2.23 ± 1.19 versus 3.36 ± 1.04 ml/min/g, p  = 0.030, respectively). Interestingly, MBF during cold pressor test did not differ between patients and controls (0.99 ± 0.20 versus 1.07 ± 0.16 ml/min/g, p  = 0.330). However, cold pressor-induced MBF response capacity was significantly lower for patients as compared to controls (1.09 ± 0.35 versus 1.44 ± 0.39 ml/g/10, 000 mmHg, p  = 0.040). Conclusions: With only partial sympathetic re-innervation of the coronary arteries, maximal dilator capacity of the coronary microvasculature and cold pressor-induced MBF response capacity remain substantially impaired in young adults after ASO compared to healthy controls. Highlights: Cardiac innervation is reduced in young adults after the arterial switch operation. Myocardial blood flow at rest and after adenosine stimulation is limited. Myocardial blood flow response capacity to a sympathetic stimulus is reduced.